Answer:
The solution to the given system of equations is (-2, -2).
Step-by-step explanation:
The given system of equations is,
2x + y = -6 .......(1)
-8x + 2y = 12 ......(2)
Now, we will make the coefficients of either x or y as opposites.
In the above system of equations, we will make the coefficients of x as opposites.
Multiplying equation (1) by '4' and equation (2) by '1', we get
8x + 4y = -24 .......(3)
-8x + 2y = 12 .......(4)
Now, we will add the equations (3) and (4).
(8x + 4y) + (-8x + 2y) = -24 + 12
⇒8x + 4y - 8x + 2y = -12
⇒6y = -12
⇒y = [tex]\frac{-12}{6}[/tex]
⇒y = -2
Now, substituting the value of y in equation (1), we get
2x + (-2) = -6
⇒2x - 2 = -6
⇒2x = -6+2
⇒2x = -4
⇒x = [tex]\frac{-4}{2}[/tex]
⇒x = -2
∴ x = -2; y = -2 is the solution of the given system of equations.